2003
DOI: 10.1063/1.1594288
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of the electromagnetic field in fully coated near-field optical probes

Abstract: Fully metal-coated near-field optical probes, based on a cantilever design, have been studied theoretically and experimentally. Numerical simulations prove that these structures allow nonzero modal emission of the electromagnetic field through a 60-nm-thick metallic layer, that is opaque when deposited on flat substrates. The far-field intensity patterns recorded experimentally correspond to the ones calculated for the fundamental and first excited LP modes. Moreover, this study demonstrates that a high confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 13 publications
(13 reference statements)
2
24
0
Order By: Relevance
“…In particular, the size of the achievable hot spot in case of radially polarized excitation (and, hence, the ultimate attainable resolution) is mostly limited by the diameter of the metal apex, which can be decreased at will. Such behaviour has been confirmed in both theoretical and experimental studies [29,40,[46][47][48][49][50] and is sketched in Figure 2.…”
Section: Nanofocusing In Snom Probes: the Axisymmetric Structuresupporting
confidence: 58%
See 1 more Smart Citation
“…In particular, the size of the achievable hot spot in case of radially polarized excitation (and, hence, the ultimate attainable resolution) is mostly limited by the diameter of the metal apex, which can be decreased at will. Such behaviour has been confirmed in both theoretical and experimental studies [29,40,[46][47][48][49][50] and is sketched in Figure 2.…”
Section: Nanofocusing In Snom Probes: the Axisymmetric Structuresupporting
confidence: 58%
“…Fully metal probes and fully metal-coated pyramidal probes with different shapes have also been analysed both in case of direct illumination at the metal apex or with far-field excitation further away from the metal apex as described in paragraph 2 [36,37,61,67] using FDTD, BOR-FDTD, finite integration technique (FIT), and the finite element method (FEM). The fully metal-coated dielectric structure which, as anticipated, is the one of interest in this chapter, has been intensively numerically investigated especially under internal back excitation and its polarizationdependent properties have been carefully examined: the need for a radially polarized excitation has been pointed out as essential to get field localization [40,[46][47][48][49][50].…”
Section: Optimization Of Probe Structures: Challenges Of Tip Modellingmentioning
confidence: 99%
“…6 The conical geometry of the probe can guide two different kinds of mode having linear or radial polarization. The radial mode is guided to the very end of the tip, while the linearly polarized mode reaches cut-off in the tapered section of the probe, and either leaks through the metal layer or is reflected.…”
Section: Published In Applied Physicsmentioning
confidence: 99%
“…4,5 The micro-fabricated SNOM probes under consideration have been studied and characterized as light emitters in theoretical and experimental works. 6,7 It has been suggested that a longitudinally polarized field confined in a small volume at the probe apex can be generated when a radially polarized mode is guided into the conical structure of the probe. The importance of such a longitudinal field in the resolution capabilities of SNOM systems has been widely demonstrated.…”
mentioning
confidence: 99%
“…Just as metallic probes under far field external illumination, they allow high field enhancement and strong confinement to an ultra-small spot whose size is mostly limited by the diameter of the metal apex (which can be sharpened at will); at the same time, they pose minor risks for sensitive samples, because of the lack of the strong deleterious background [8,10,11,[14][15][16]. However, such desirable properties can be obtained only under a radially polarized excitation, which unfortunately requires an injection procedure extremely sensitive to misalignments [17].…”
Section: Introductionmentioning
confidence: 99%